Geographical cluster and performance: The case of Iberian ham - Diez-Vial, Isabel (Food Policy, 2011)
This research examined whether ﬁrms that concentrate geographically perform better or worse than their more dispersed counterparts. While belonging to a cluster may have positive externalities for proximate ﬁrms, there can also be congestion economies that counterbalance these advantages. Having identiﬁed existing ham-producing establishments in the Iberian ham cluster, a sample of 265 ﬁrms was selected and it was conﬁrmed that as the number of neighbouring ﬁrms increases performance increases. Also, the proximity to larger ﬁrms in the same province beneﬁt smaller ﬁrms. This positive effect that geographical concentration has on performance is explained by access to valuable natural resources, workers, higher demand, knowledge spillovers, and lower transaction costs, which may help managers and policy-makers in their investment decisions, as well as contributing to the dearth of existing research and its contradictory nature.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Congestion costs; geographical concentration; Ham producers; Local externalities